(untitled) (Modern information system and technologies, 2018)
The results of simulation of antennas on fractal basis are presented in the work. Due to the complexity of describing the interaction of non-Euclidean geometry antennas with radio waves, their synthesis was performed using the MMANA-GAL program. The proposed sequence of simulation steps allows for multi-bandwidth and broadband. On the basis of the conducted researches recommendations on practical application of fractal structures in the interests of systems and networks 802.11х and 5G are offered.